Synthesis and reducing power assay of methyl semicarbazone derivatives - Manmohan Singhal; Arindam Paul; Hemendra P. Singh (Journal of Saudi Chemical Society, 2014)
In the present study we have designed a new pharmacophore ‘Chalconesemicarbazone’ by pharmacophore hybridization approach of drug design. A series of novel chalconesemicarbazones was synthesized and evaluated for their antioxidant activity by reducing power assay. Most of the compounds were found to be potent antioxidants. Free radicals play an important role in various pathological and xenotoxic effects so antioxidant may have protective role in these pathological conditions. Based on the results of reducing power assay 1-[1-(2,4-dihydroxyphenyl)-3-(2-hydroxyphenyl)allylidene]-4-(4-methylphenyl)semicarbazide (compound 18) and 1-[1-(2,5-dihydroxyphenyl)-3-(6-hydroxyphenyl)allylidene]-4-(4-methylphenyl)semicarbazide (compound 21) were the most active lead compounds. It was found that methoxy and hydroxyl substituted chalconesemicarbazones exhibited potent reducing power and unsubstituted compound showed less reducing potential.